Influência do ensino superior em grupos de Startups no Brasil: abordagem com análise de redes sociais e dados da Web - Nardelli, Júlio César Borges da Silveira (2020)
This research examined the influence of Higher Education Institutions (HEI) in groups of startups in Brazil. First, the literature was organized in works that used traditional methodologies and others that used Social Network Analysis (SNA). Then, data sources available on the Web, ways to obtain and store them were selected. After that, an examination was carried out at the national level of the types of entrepreneurial activities and the geographic location of the startups’ hubs. Finally, SNA was used in an alumni network formed by the founders of startups to measure the impact of HEIs on this structure. The examination of entrepreneurial activities revealed that regional variations could be favoring certain sectors and generating opportunities. Although startups are concentrated in more economically developed hubs such as capital cities, there are hubs outside of them and startups distributed in several locations. This provides evidence that entrepreneurship spreads easily across the country. When considering a structure of cognitive social connections, as in the alumni network’s case, the geographical distance does not prevent the actors from relating because the connections depend more on the similarity of subjects and the exchange of knowledge than on geographic proximity. Thus, the range of influence of HEIs reaches inter-municipal limits between 250 and 500 km and even inter-regional in some cases, with distances above 1000 km. Through the investigation of the network structure, it was observed that the educational function is distributed among universities, colleges, and university centers, considering public and private HEIs, and each element presents different ways of interacting with the startups’ network. Although the General Index of Courses (GIC) is an important instrument for assessing the quality of HEIs in Brazil, it showed a weak correlation with the centrality of HEI degree in the network. This means that other factors influence the position of the HEI within the structure and the formation of the cluster around it. The education of the founders is also an element that deserves attention. For example, the period at college represents an important moment in the entrepreneur’s formation because it represents the largest share of the degrees in the analysis. The founders also continue to seek to deepen their studies even after creating a startup; therefore, the higher education system must be prepared to receive them and meet their expectations and needs in the best possible way. This research seeks to justify the importance of the higher education network within the infrastructure supporting Brazilian entrepreneurship. It can influence public policies, such as the Ministry of Education’s “Future-se” program that brings new perspectives on the role of teaching and research in Brazil, mainly for federal universities. In general, this work contributes to education, entrepreneurship, and public policies.